COMPETENCE IMPROVEMENT OF POLRI EDUCATORS THROUGH SPREADING TRAINING - Mamay Sumarna (IKIP Siliwangi Bandung, 2018)
The development of science and technology today demands changes and a better and more mature working mechanism in anticipating every challenge in the community. This also applies to the Indonesian National Police. Therefore, competencies and abilities must always be developed and improved. Therefore, the Cisarua National Police School (SPN), West Java Regional Police is trying to develop various competencies needed to address the challenges and needs of the community. Not only for students but also for educators at the Cisarua National Police, West Java Regional Police, through a refresher training program. The theoretical basis used for this theory is the theory of education outside of school, theory of education and training. The method used in this research is descriptive qualitative with the instrument of interview guidance, documentation study and observation. The results of this study found that the refresher training planning was carried out by identifying the needs and availability of available resources, the implementation of refresher training using a humanist approach, demontrative methods and practice where police educators at the Cisarua National Police in West Java Regional Police are expected to be able to follow the program to be able to provide direction and understanding the competence and capability of the Indonesian National Police in the community, while the evaluation in this activity was carried out to be able to provide feedback in the implementation of future activities. The obstacles encountered were not directly seen to have a significant impact, however, there were several obstacles, namely learning methods that needed to be strengthened, instruments and learning media that needed to be developed in order to answer the needs of the trainees. The general conclusion of this study is the refresher training in the Cisarua NES, West Java Regional Police, has provided an opportunity to develop, improve and maintain the competence of the teaching staff at the Cisarua National Police in West Java Regional Police.